Erosive pustular dermatitis of the scalp - Czajkowska, Anna; Węgłowska, Jolanta B.; Cygan, Katarzyna (Dermatology Review/Przegląd Dermatologiczny, 2015)
Introduction. Erosive pustular dermatitis of the scalp is rarely diagnosed due to the uncharacteristic histopathological picture, while clinical manifestations are similar to many other dermatoses. To date, 40 cases of this disease have been described. The lesions occur most often in the elderly, triggered mainly by UV radiation, trauma and infections. The disease course is chronic, with periods of exacerbation and remission. Eruption subsides with scarring and permanent loss of hair. Objective. Presentation of a case of erosive pustular dermatosis of the scalp observed and treated in our center. Case report. We present a case of a 74-year old man with erosive pustular dermatosis of the scalp (EPDS) with pruritic and painful pustules, crusts and erosions on an erythematous base, located in the frontal, parietal, and temporal area. The diagnosis of EPDS was established on the basis of clinical manifestations after thorough differentiation with other dermatoses. A good therapeutic effect was achieved after topical treatment with corticosteroids and tacrolimus. Conclusions . Our case indicates that the diagnosis of EPDS may be difficult and should be made after exclusion of other dermatoses involving the scalp.